AB0147 A study of adipokines' level in patients affected by systemic sclerosis. (23rd January 2014) - Vasile, M.; Neumann, E.; Mueller-Ladner, U.; Stefanantoni, K.; D'Aluisio, D.; Valesini, G.; Riccieri, V.
Abstract : Background: Systemic sclerosis (SSc) is a connective tissue disorder characterized by progressive fibrosis of the skin and remodeling of the microvasculature. Increased extracellular matrix deposition by fibroblasts affects most internal organs. Adipokines such as adiponectin, resistin and leptin are immunomodulatory cytokine-like mediators (1 ). They seem to be able to contribute to the tissue damage in some connective tissue diseases but little is known about their role in SSc (2 ). Objectives: The present study analyzed adipokines' levels in the sera of SSc patients and their possible correlations with clinical parameters Methods: Blood samples of 59 SSc patients and 23 healthy controls were collected. Adiponectin and resistin were measured by commercially available ELISA kits, while leptin was measured by a Bioplex Pro Assay kit. In all patients modified Rodnan Skin score (mRSS), nailfold capillaroscopy, number of digital ulcers, cardiac, lung, articular and gastrointestinal involvements were evaluated. Results: We found a trend to lower adiponectin levels in SSc patients in comparison to healthy controls (13.577 mg/ml vs 15.31 mg/ml; p<0.07) whereas resistin levels were significantly lower (12.88 pg/ml vs 16.02 pg/ml; p< 0.03) while leptin levels were significantly higher (57.88 ng/ml vs 17.63 ng/ml; p<0.004). Moreover we found significantly lower adiponectin levels in those patients with a higher skin score (14.651 mg/ml vs 11.316 mg/ml; p<0.05). A trend to decreased levels of adiponectin was also observed in patients with digital ulcers and with articular involvement (10.912 mg/ml vs 1.5 mg/ml, p<0.07; 11.653 mg/ml vs 15.414 mg/ml, p<0.07 respectively). Conclusions: In SSc patients adipokines serum levels differ from those of healthy subjects. Adiponectin and resistin seem to be down-regulated, as if they could have a protective role, as confirmed by a higher skin score in those cases with lower adiponectin levels. Besides leptin is up-regulated, confirming its role as a potentially pro-inflammatory cytokine in many connective tissue diseases (3 ). However their different behavior deserve deeper investigations to better understand their role in SSc References: Lago F, Dieguez C et al 2007: Adipokines as emerging mediators of immune response and inflammation. Nature Clinical Practice Rheumatology 2007, vol. 3: 716-24. Lakota K, Jun W et al 2012: Levels of adiponectin, a marker for PPAR-g activity, correlate with skin fibrosis in sistemi sclerosis: potential utility as biomarker? Arthritis Research&Therapy 14:R102 Vadacca M, Margiotta D et al 2008. Adipokines and Systemic Lupus Erythematosus: Relationship with Metabolic Sindrome and Cardiovascular Disease Risk Factors . J Rheumatol 36:295-7. Disclosure of Interest: None Declared